2008
DOI: 10.1007/s00436-008-1088-z
|View full text |Cite
|
Sign up to set email alerts
|

Contracaecum pyripapillatum n. sp. (Nematoda: Anisakidae) and a description of C. multipapillatum (von Drasche, 1882) from the Australian pelican, Pelecanus conspicillatus

Abstract: A new species of nematode, Contracaecum pyripapillatum, is reported from the Australian pelican, Pelecanus conspicillatus. This species resembles Contracaecum multipapillatum which was found in the same host. These two species can be differentiated from one another based on the shape of the preanal papillae, being pyriform in C. pyripapillatum and circular in C. multipapillatum. Genetically, the two species differ in the sequences of first and second internal transcribed spacers (ITS-1 and ITS-2, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 13 publications
1
64
0
Order By: Relevance
“…The sequence and phylogenetic analyses showed that the nematode larvae investigated in this study are closely related to C. multipapillatum, which is a species complex and it was shown that it consists of at least 4 distinct species found in the USA, Europe, and Australia (Nadler, D' Amelio, Fagerholm, Berland, & Paggi, 2000;Mattiucci, Turchetto, Bragantini, & Nascetti, 2002;D'Amelio et al, 2007;Shamsi et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The sequence and phylogenetic analyses showed that the nematode larvae investigated in this study are closely related to C. multipapillatum, which is a species complex and it was shown that it consists of at least 4 distinct species found in the USA, Europe, and Australia (Nadler, D' Amelio, Fagerholm, Berland, & Paggi, 2000;Mattiucci, Turchetto, Bragantini, & Nascetti, 2002;D'Amelio et al, 2007;Shamsi et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…1 (Accession numbers KF990491), isolated from the body cavity and the intestines of H. forskahlii and T. zillii in Lake Turkana, Kenya (Otachi, Szostakowska, Jirsa, & Fellner-Frank, 2015). The last in turn draw an analogy (89%) to the Contracaecum multipapillatum (von Drasche, 1882) from the Australian pelican Pelecanus conspicillatus (Accession numbers AM940056) (Shamsi et al, 2008). In addition, ITS-2 from the same larvae showed the highest similarity (86%) to three ITS-2 sequences of Contracaecum L3 (Accession numbers FM210437-FM210438-FM210439) from Iranian fish (recorded by Shamsi in 2008 to the GenBank).…”
Section: Sequence and Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using suitable genetic markers, electrophoretic and sequencing methods can overcome this limitation [15]. A number of studies have demonstrated that the first and second internal transcribed spacers (ITS-1 and ITS-2, respectively) of nuclear ribosomal DNA (rDNA) provide suitable genetic markers for the identification of anisakid species, irrespective of developmental stage [16][17][18][19][20][21][22][23][24][25][26][27], and PCR-coupled mutation scanning of the ITS-1 and/or ITS-2 combined with targeted sequencing [28] provides a powerful approach for exploring the genetic composition of anisakid populations and for investigating their biology.…”
Section: Introductionmentioning
confidence: 99%
“…Upon examination, they were identified as Contracaecum sp. (Ascaridida: Anisakidae) [5][6][7] ( Fig. 1.B and 1.D).…”
Section: A228mentioning
confidence: 98%